Perception of politeness in English requests by Thai EFL learners - Boonjeera Chiravate, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Requesting someone to do something that is beneficial to the speaker but costly to the hearer, involves the use of politeness strategies. The present study aims to investigate to what extent Thai EFL learners differ from native speakers of English in the use of politeness strategies and if there is evidence of L1 influence on the learners’ use of politeness strategies. The participants were 30 native speakers of American English and 60 Thai EFL learners divided into two groups: high-proficiency (30) and low-proficiency (30). To examine their perception of politeness levels of different English request forms, a judgment task consisted of 12 situations varying in social and psychological factors was developed. Each of the situations had six politeness strategies in making requests. The participants were asked to choose only one politeness strategy which they would be most likely to use in a given situation. The results show that the learners’ use of politeness strategies is dissimilar to that of native speakers. The native speakers used more polite strategies, whereas the learners tended to use less polite strategies. Compared to the high-proficiency learners, the low-proficiency learners differed from the NS to a greater extent. In certain situations, the difference in the use of politeness strategies between the native speakers and the learners can be attributed to L1 influence. The analysis shed light on the difficulty experienced by L2 learners in acquiring aspects of L2 pragmatics.